Leoneses en la Habana en el siglo XX - Blanco Rodríguez, Juan Andrès (Estudios humanísticos. Geografía, historia y arte, 1993)
The independence of Cuba did not end the flow of Spaniards emigrating to the largest island in the West Indies. For this reason during the first thirty years of this century a large number of Spanish associations developed in Cuba. In 1909 the Centro Castellano was founded and over the next decade a series of associations linked with it emerged. Their aim was to bring together Spanish residente proceeding from some of the provinces of the present Castilla y León region, providing them with cultural and recreational activities as well assistance and welfare. The Colonia Leonesa de Cuba is one of them and contibutes to maintain the relationship between the people from León resident in Cuba and their descendants and also their links with the province of León.